Preparation method of high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite material coating

Through powder metallurgy and friction stir coating processes, combined with ultrasonic assisted technology, the problem of difficulty in depolymerization and dispersion and harmful reactions in the preparation process of nanodiamond-reinforced aluminum-based composite materials is solved, and a high hardness and high wear resistance material preparation is achieved.

CN116397227BActive Publication Date: 2025-04-15GUANGXI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310350459.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-04
Publication Date
2025-04-15
Estimated Expiration
2043-04-04

AI Technical Summary

Technical Problem

During the preparation process, nanodiamond-reinforced aluminum-based composites have problems such as difficulty in depolymerization and dispersion and harmful reactions with aluminum to form Al4C3 phase, resulting in poor material performance.

Method used

The process of powder metallurgy + friction stir coating is adopted, and through ball milling, hot pressing, sintering and hot extrusion, combined with ultrasonic assisted technology, the uniform dispersion of nanodiamond and good combination with aluminum are achieved to avoid the formation of Al4C3.

Benefits of technology

A high hardness and high wear resistance nanodiamond reinforced aluminum-based composite coating was obtained, which significantly improved the hardness and wear resistance of the material, and was suitable for mass production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005312989090000061
    Figure GDA0005312989090000061
  • Figure GDA0005312989090000071
    Figure GDA0005312989090000071
  • Figure GDA0005312989090000072
    Figure GDA0005312989090000072
Patent Text Reader

Abstract

The invention discloses a method for preparing a high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite material coating, which belongs to the technical field of aluminum-based composite materials. The composite material has the following chemical components by weight percentage: pure aluminum or aluminum alloy: 98.5-99.5%, nano-diamond: 0.5-1.5%. The composite material preparation method of the invention includes two parts. One is the preparation of composite material hot extrusion profiles: mainly through hot pressing, sintering and hot extrusion forming at one time, and a dense composite material is prepared under high temperature and high pressure conditions. The second is to prepare a high-hardness and high-wear-resistant coating by friction stirring coating of the composite material. The coating method has the characteristics of strong bonding between the coating and the substrate, uniform dispersion of the nano-diamond reinforcement, fine and uniform grains of the coating material, high hardness and good wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of material science and engineering technology, and specifically relates to a diamond-reinforced aluminum-based composite material and a preparation method thereof. Background Art

[0002] Compared with one-dimensional carbon nanotubes and two-dimensional graphene, zero-dimensional nanodiamond (ND) has a unique sp2@sp3 core-shell structure, with a hard sp3 hybridized carbon structure similar to diamond in the core, and a layer of sp2 hybridized carbon and various functional groups similar to fullerene in the shell. This unique structure gives ND excellent properties, including very high hardness, excellent thermal conductivity, high wear resistance and chemical stability. The superior performance of diamond, coupled with its very small size (2-10nm) and unique surface structure, makes ND an ideal reinforcement for reinforcing metal matrix composites. Recently, some studies have reported that ND has extremely high reinforcement efficiency and has great potential to solve the trade-off between strength and ductility of composite materials, and has great advantages in improving the hardness and tribological properties of composite materials. However, these studies are not very focused on aluminum, and the preparation methods used are complex, with high requirements for equipment and high preparation costs, and do not have the conditions for mass production. There are two biggest difficulties in preparing nanodiamond reinforced aluminum matrix composites. One is the difficulty of depolymerization and dispersion. Nanodiamonds have extremely high surface energy and complex dangling bonds, which make them very easy to agglomerate. The size of the agglomerates is usually between 50-500nm, and it is more difficult to deagglomerate when the agglomerates are less than 100nm. Since nanodiamonds are easy to agglomerate, it is difficult to evenly disperse them in the composite material, resulting in uneven microstructure of the material, thereby deteriorating the material performance. Moreover, the agglomerates in the composite material are prone to microcracks when subjected to stress, which can easily cause the material to fail prematurely. Second, it is easy to react with aluminum to generate harmful Al4C3 phases. Al4C3 easily absorbs water and decomposes, causing the material to fail. The reaction temperature of aluminum and nanodiamonds is about 550°C, while the melting point of aluminum is about 660°C. Therefore, nanodiamond-reinforced aluminum-based composite materials are difficult to process through more convenient and economical liquid processing methods (such as stirring casting). To this end, the present invention uses a process method of powder metallurgy + friction stir coating to obtain a nanodiamond-reinforced aluminum-based composite material with high hardness and high wear resistance.

[0003] Powder metallurgy is a common, economical, environmentally friendly and mature process for preparing composite materials. Conventional powder metallurgy sintering needs to be carried out in a vacuum environment, which not only has high manufacturing costs, but also is difficult to perform high-pressure compression, and the pressure is usually below 150MPa. Since the nano-diamond reinforced aluminum-based composite material needs to be carried out below 550°C (the melting point of aluminum is 660°C), the aluminum powder is not melted at this time, and the nano-diamonds embedded in the surface of the aluminum particles or adsorbed on the surface of the aluminum particles easily block the bonding between the aluminum particles, so a very high pressure is required to obtain a dense structure. Conventional sintering equipment and sintering processes are not suitable. Hot extrusion is a common economical and environmentally friendly material preparation method for obtaining profiles, and is often used in the preparation of light metal profiles such as aluminum and magnesium. Through hot extrusion, the composite material can not only obtain the desired shape and size, but also increase the bonding force of the material, eliminate micropores, improve the uniformity of the reinforcement phase dispersion, and improve the comprehensive performance of the material. However, experiments show that the composite material obtained by hot extrusion has a high content of nano-diamonds in some areas and a low content in some areas. The uneven dispersion leads to uneven microstructure of the material and unsatisfactory mechanical properties.

[0004] Therefore, the present invention, based on the preparation of primary materials by hot extrusion, uses a severe plastic deformation process and friction stirring coating to coat the composite material onto the substrate while re-dispersing the nano-diamonds.

[0005] Friction stir coating technology is the development and specific application of additive friction stir deposition technology. Additive friction stir deposition (AFSD) is an emerging solid-state SPD method that has been applied to 3D printing and the repair of metals and composites. It combines the concept of additive manufacturing with the principle of friction stirring, relying on the thermal mechanical energy of friction stirring to soften the material, and then depositing it layer by layer to form a three-dimensional structural part. Compared with friction stir welding (FSW), AFSD does not use a stirring needle, but a hollow stirring tool. The material to be deposited is fed into the friction stirring work area through the hole of the stirring tool. When the material to be deposited is pushed into the friction stirring work area, the dynamic contact friction between the deposited material and the stirring tool head above it and the substrate below generates a lot of heat. The deposited material and the substrate or the material and the material are firmly combined due to the intense friction. The stirring tool deposits the material layer by layer according to the planned route, so that three-dimensional parts can be directly constructed. In addition, during AFSD processing, the material undergoes high plastic strain and rate of change, as well as a drastic temperature change from room temperature to near melting temperature. The AFSD process is accompanied by violent material flow, dense dislocation generation and recombination. The deposited material has the characteristics of no micropores or microcracks and fine grains like forged materials, avoiding most defects in the casting process. In addition, under the action of high temperature, high-speed material flow and violent dislocation evolution, the AFSD process greatly promotes the dissolution of aluminum alloy precipitation phase and the reprecipitation of solid solution. However, research on AFSD is still in its infancy. Previous research has mainly focused on pure metals and alloy materials, and the improvement of material properties is limited. There is almost no research on composite materials, let alone on nanoparticle-reinforced aluminum-based composites. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a method for preparing a high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite coating. The obtained composite coating has high hardness and high wear resistance and has good application prospects.

[0007] To achieve the above objectives, the following solutions are provided:

[0008] A method for preparing a high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite material coating comprises the following steps:

[0009] (1) weighing nano-diamond and aluminum powder raw materials according to the ratio, and then loading the powder raw materials into a steel can, placing the steel can into a ball mill, and ball milling under an inert gas atmosphere, adding 1%-2.5% stearic acid as a control agent to the ball milled powder to prevent the powder from sticking to the steel can or steel balls; ball milling and mixing to obtain a mixed material powder;

[0010] (2) heating the mixed material powder to 280-430° C. and keeping the temperature for 1 hour to degas;

[0011] (3) The mixed material is then placed in a powder cylinder of a sample preparation device, heated to 120°C-150°C and dried for 20-30 minutes, and then the powder is compressed under a pressure of 400 MPa;

[0012] (4) Heating to 480°C, keeping the temperature for 20-30 min, applying a pressure of 790 MPa for the first compression, then heating to 500-540°C, keeping the temperature for 20-30 min, and then applying a pressure of 790 MPa for the second compression;

[0013] (5) opening the powder cylinder of the sample preparation device, inverting the composite material blank treated in step (4), heating and controlling the temperature to 450-510° C., keeping the temperature for 20-30 min, and then placing it under a press for hot extrusion; thus, a hot extruded profile of a nano-diamond reinforced aluminum-based composite material can be obtained;

[0014] (6) processing the hot extruded profile of the nano-diamond reinforced aluminum-based composite material into a coated rod;

[0015] (7) Place the coating rod into the center hole of the friction stir coating device and adjust the height of the machine tool so that the coating rod contacts the substrate;

[0016] (8) starting the machine tool of the friction stir coating device and performing coating processing according to the set coating parameters; the coating parameters are a translation speed of 24-25 mm / min, a downward speed of 7-10 mm / min, and a rotation speed of 5000-9000 r / min;

[0017] (9) After coating, the substrate is taken out and cooled naturally. The coating operation is completed, and a high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite material coating is obtained.

[0018] The raw materials of the invention are calculated by weight percentage as follows: Al: 98.5-99.5%, nano diamond: 0.5-1.5%.

[0019] The aluminum in the raw material of the present invention can be provided by pure aluminum, aluminum or aluminum alloy materials such as AA6061, AA7075, AA2024, etc.

[0020] Furthermore, the ball material of the ball mill in step (1) is steel ball, and the ball milling parameters are: rotation speed of 500-600rpm / min, alternating time of 10-15min, ball-to-material ratio of 8-10:1, ball milling time of 8-9h, and inert gas of argon. As the optimal parameters, the rotation speed is 500rpm / min, the alternating time is 15min, the ball-to-material ratio is 10:1, and the ball milling time is 9h.

[0021] Furthermore, the degassing in step (2) can be performed in a vacuum environment or in the air. Aluminum powder oxidizes very slowly at temperatures below 500°C, so a degassing temperature of 280-430°C will not increase the oxidation of aluminum powder.

[0022] Furthermore, the specific steps of step (3) are as follows: before placing the material, first place two pads at the bottom of the powder cylinder, place a 2-5 mm thick graphite powder layer between the two pads, compress the graphite powder with a pressure of 200-300 MPa to increase the sealing, and stick a layer of graphite paper on the inner wall of the powder cylinder to reduce friction; after placing the mixed material, first place the upper pressure pad, and then place a layer of 2-5 mm thick graphite powder on the upper pressure pad to increase the sealing, heat to 120°C-150°C and dry for 20 minutes, then place a push rod to compress, and compress the mixed material powder with a pressure of 400 MPa for 1-5 minutes.

[0023] Furthermore, the specific steps of step (4) are as follows: first, the temperature is raised to 480°C, kept warm for 30 minutes, and a pressure of 790 MPa is applied for the first compression, and the compression time is 1-5 minutes; then the temperature is raised to 500-540°C and kept warm for 30 minutes; then a pressure of 790 MPa is applied for the second compression, and the compression time is 1-5 minutes.

[0024] The purpose of the present invention to compress the mixed material twice is to reduce the oxidation of aluminum powder. The oxidation rate of aluminum powder is very slow below 500°C, but it is very fast above 550°C, and it is also easy to react with nano diamonds to generate Al4C3 compounds to reduce the material performance. Therefore, the first compression is controlled to be carried out below 500°C to compact the material and enhance the density of the two end faces, which is conducive to sealing and preventing and slowing oxidation; the second compression strengthens the full bonding of the internal aluminum particles, making the material more dense, further preventing and reducing the oxidation process, and no Al4C3 compounds are generated during the preparation process.

[0025] Furthermore, the specific steps of step (5) are as follows: remove the heating sleeve of the sample preparation device, then remove the cushion block, place the powder tube directly on the support block, align the center of the powder tube with the support block, start the lower pressure rod of the press, push out the two pressure pads at the bottom of the barrel, then reverse 180°, use the pressure rod to press the composite material blank back to the middle, then put the profile mold into the powder tube, install the cushion block, reverse 180°C and place it on the support block, align the centers, put down the heating sleeve, reheat to 450-510°C, keep warm for 30 minutes, and then put it into the press for hot extrusion.

[0026] Furthermore, the present invention pushes out all the pressure pads, extrusion residual blanks, and profile molds in the powder tube after hot extrusion to obtain the nano-diamond reinforced aluminum-based composite material. The specific steps are: remove the heating pad cover, remove the pad under the powder tube, and turn the support block 180 degrees upside down with the large hole facing upward. Put down the powder tube and align the center. Use a pressure rod on the press to squeeze all the pressure pads, extrusion residual blanks and molds in the powder tube out of the powder tube. Remove the profile mold. Restore the sample preparation device. After restoration, the second sample can be prepared.

[0027] Furthermore, the coating rod matches the inner hole shape of the friction stir coating tool head, and the size is, for example, 4.9*4.9*20 mm. The size can be adjusted according to the device structure.

[0028] Furthermore, in the step (7), the gap between the coating tool head of the friction stir coating device and the substrate is pre-adjusted to a distance of 0.2-1.5 mm, which is consistent with the desired coating thickness.

[0029] Furthermore, the method further includes connecting an ultrasonic auxiliary device to the friction stir coating device before step (8), and using an ultrasonic generator of the ultrasonic auxiliary device to vibrate the substrate mounted on the friction stir coating device.

[0030] Furthermore, when the frequency range of the ultrasonic generator is 20k±400Hz and the rated power is 2kW and the amplitude ratio of the ultrasonic generator is adjusted to 50%-80%, the corresponding measured amplitude is in the range of 10-40μm.

[0031] The sample preparation device of the present invention can adopt the sample preparation device of alloy composite materials currently available in the market. The powder cylinder and the cushion block of the sample preparation device can be made of high temperature resistant material H13 and be heat treated and quenched. There is a temperature detection hole on the powder cylinder. The pressure pad and the pressure rod are made of high temperature resistant material SKH51-59 and are heat treated and quenched. The profile mold used in the hot extrusion process can be made of SKH51-59 and be heat treated and quenched.

[0032] The coating principle of the present invention is as follows: Friction stir coating relies on the friction between the coating rod, the substrate and the coating tool head to generate heat to soften the material, but the temperature does not reach the melting point of the material. It is coated on the substrate by solid-state welding. Since the material is in a solid state, the violent plastic deformation generated during coating causes the local weak parts inside the material to be segmented, refined and strengthened, resulting in a more uniform and fine grain structure, and the strengthening phase particles inside the composite material are evenly dispersed, thereby improving the strengthening effect of the strengthening phase.

[0033] As an optimization of the solution, the present invention can also add ultrasonic assisted coating, and its principle is: ultrasonic assisted friction stir coating relies on the friction between the coating rod and the substrate and the coating tool head and ultrasonic vibration to soften the material, but the temperature does not reach the melting point of the material. It is coated on the substrate through solid-state welding. Since the material is in a solid state, the severe plastic deformation generated during coating causes the local weak parts inside the material to be divided, refined and strengthened, resulting in a more uniform and fine grain structure. Due to the action of ultrasound, the material is easier to soften, the material has better fluidity, the grain refinement effect is better, the structural uniformity is better, and the bonding with the substrate is better, so the hardness and wear resistance of the material are better than those of conventional friction stir coating.

[0034] The present invention has the following beneficial effects:

[0035] 1. The present invention adds nanoparticle reinforcement, which improves the hardness and wear resistance of the composite material by combining with the matrix Al. The addition of nanodiamonds increases the dislocation density of the material during deformation, refines the grains, and improves the hardness. In the experiment, AA6061 was used as the substrate. After friction stir coating, the hardness of the AA6061 coating can reach about 82.1HV; the coating with a nanodiamond content of 1.5wt.% can reach a hardness of 135.3HV, which is an increase of 62.4%. After ultrasonic-assisted friction stir coating, the hardness of the AA6061 coating can reach about 106.4HV, and the coating with a nanodiamond content of 1.5wt.% can reach a hardness of 164.1HV, which is harder than ordinary 304 stainless steel hard materials.

[0036] 2. The high-hardness and high-wear-resistant aluminum-based composite coating of the present invention can be coated on soft aluminum plates, greatly improving the wear resistance of ordinary aluminum plates. Taking AA6061 as the substrate, a 1.5wt.% ND / AA6061 composite coating prepared by ultrasonic-assisted friction stir coating process forms a Cr-rich mechanical mixed layer on the coating surface in a wear test with Gr15, and the wear rate of the coating is only 50% of that of the friction stir coated AA6061 coating.

[0037] 3. The present invention adopts a powder metallurgy method to firstly perform high-speed ball milling on the material, obtain a good dispersion effect by high-speed ball milling of nano diamond particles and aluminum powder, thereby improving the performance of the composite material, and then perform hot pressing, sintering and hot extrusion to obtain the composite material. Hot pressing, sintering and hot extrusion are all formed at one time, and vacuum equipment is not required but still has good sealing performance, which can prevent material oxidation, and a dense composite material is obtained when used under high temperature and high pressure conditions.

[0038] 4. The method of the present invention adopts a two-step heating and pressurizing method during the overheating and pressing sintering process, first at 480°C, keep warm for 30 minutes, pressurize at 790MPa for the first compression; then heat to 500-540°C and keep warm for 30 minutes; then pressurize at 790MPa for the second compression. The method of heating in steps and gradually pressurizing is adopted. The first compression can fully compact the material, enhance the density of the two end faces of the material, facilitate sealing, and prevent the material from being oxidized when heated to 540°C. The second heating to a higher temperature strengthens the full bonding of the internal aluminum particles, making the material more dense, and no Al4C3 compounds are produced during the preparation process.

[0039] 5. The nano-diamond reinforced aluminum-based composite material of the present invention is used as a coating rod and is obtained by friction stir coating or ultrasonic assisted friction stir coating. The coating has a strong bonding force with the substrate and the average equivalent diameter of the deposited coating grains is less than 1 μm, belonging to an ultrafine grain structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a comparison of the friction stir coating effects of 0.5% ND / AA6061 composite materials. The left side is the coating without ultrasonic coating, and the right side is the coating with ultrasonic coating.

[0041] Figure 2 The hardness distribution diagram of the coating after friction stir coating. The left figure is the hardness distribution diagram along the thickness direction, and the right figure is the hardness distribution diagram along the horizontal direction.

[0042] Figure 3 The left figure shows the hardness distribution of the coating after ultrasonic assisted friction stir coating. The right figure shows the hardness distribution along the thickness direction, and the left figure shows the hardness distribution along the horizontal direction.

[0043] Figure 4 This is a comparison chart of the wear rates of the six coatings of the present invention.

[0044] Figure 5 Surface after friction and wear test of ultrasonic-assisted 1.5% ND / AA6061 coating.

[0045] Figure 6 EBSD images of hot extruded profiles, where (a) is AA6061 and (b) is 0.5% ND / AA6061.

[0046] Figure 7 Microstructure diagram of the coating, where (a) AA6061; (b) 0.5% ND / AA6061.

[0047] Figure 8 Figure 2 is a diagram of the coating bonding interface, where (a) and (b) are optical microscope photos of the coating bonding interface; (c) and (d) are EBSD images of the coating bonding interface. DETAILED DESCRIPTION

[0048] The present invention is further described below by way of examples to make the advantages and features of the present invention more easily understood, but the protection scope of the present invention is not limited to these examples.

[0049] The aluminum element in the embodiment of the present invention is provided by AA6061 aluminum alloy, which is purchased from Beijing Zhongke Yannuo New Material Technology Co., Ltd., with a particle size of 30 microns. Nanodiamond is purchased from Heyuan Zhonglian Nanotechnology Co., Ltd., with a particle size of 2-10 nanometers, with an average of 6 nanometers.

[0050] Example 1

[0051] The nano-diamond reinforced aluminum-based composite material hot extrusion profile has the following chemical components by weight percentage: AA6061: 100%, nano-diamond (Nanodiamond): 0%.

[0052] The method for preparing a nano-diamond reinforced aluminum-based composite material hot extrusion profile comprises the following steps:

[0053] (1) Nano-diamond and AA6061 aluminum alloy powder raw materials were weighed according to the above ratio, and the powder raw materials were then loaded into a steel can, which was placed in a ball mill, and 2% stearic acid was added as a control agent to prevent the powder from sticking to the steel can or steel balls; the mixed material powder was obtained by ball milling in an argon atmosphere; the ball material used in the ball mill was steel balls, and the ball milling parameters were: rotation speed of 500 rpm / min, alternating time of 15 min, ball-to-material ratio of 10:1, and ball milling time of 9 h.

[0054] (2) The mixed material powder is heated to 430°C under vacuum and kept at this temperature for 1 hour to degas.

[0055] (3) Before placing the material, first place two pads at the bottom of the powder cylinder of the sample preparation device, place a layer of graphite powder about 2 mm thick between the two pads, compress the graphite powder with a pressure of 200 MPa to increase the sealing, and stick a layer of graphite paper on the inner wall of the powder cylinder to reduce friction; then put the mixed material into the powder cylinder, put in the upper pressure pad, and then put a layer of graphite powder about 2 mm thick on the upper pressure pad to increase the sealing, heat to 150°C and dry for 20 minutes, then put in the upper pressure pad, and then put a layer of graphite powder 2-5 mm thick on the upper pressure pad to increase the sealing, put in the push rod for compression, and compress the mixed material powder with a pressure of 400 MPa for 1-5 minutes.

[0056] (4) First, the temperature is raised to 480°C, kept at this temperature for 30 minutes, and a pressure of 790 MPa is applied for the first compression for 1-2 minutes; then the temperature is raised to 530°C and kept at this temperature for 30 minutes; then a pressure of 790 MPa is applied for the second compression for 1-2 minutes.

[0057] (5) Remove the heating sleeve of the sample preparation device, then remove the cushion block, place the powder cylinder directly on the support block, align the center of the powder cylinder with the support block, start the lower pressure rod of the press, push out the two pressure pads at the bottom of the barrel, then reverse 180°, use the pressure rod to press the composite material blank back to the middle, then put the profile mold into the powder cylinder, install the cushion block, reverse 180° and place it on the support block, align the centers, put down the heating sleeve, reheat to 480°C, keep warm for 30 minutes, and then put it into the press for hot extrusion to obtain the hot extruded profile of nanodiamond reinforced aluminum-based composite material, recorded as: AA6061.

[0058] Example 2

[0059] The nano-diamond reinforced aluminum-based composite material hot extrusion profile has the following chemical components by weight percentage: AA6061: 99.5%, nano-diamond (Nanodiamond): 0.5%. The preparation method and parameters of the hot extrusion profile are the same as those in Example 1, and the obtained nano-diamond reinforced aluminum-based composite material hot extrusion profile is recorded as: 0.5% ND / AA6061.

[0060] Example 3

[0061] Nanodiamond reinforced aluminum-based composite material hot extrusion profile, the chemical components by weight percentage are Al: 97.5%, nanodiamond (Nanodiamond): 1.5%. Preparation method of hot extrusion profile The preparation method and parameters are the same as those in Example 1, and the obtained nanodiamond reinforced aluminum-based composite material hot extrusion profile is recorded as: 1.5% ND / AA6061

[0062] Mechanical hardness test of hot extruded profiles of nano-diamond reinforced aluminum matrix composites:

[0063] The hot extruded profiles of the nano-diamond reinforced aluminum-based composite materials obtained in Examples 1-3 were subjected to mechanical property tests according to conventional methods. The test results are shown in Table 1.

[0064] Table 1 Hardness test results of nano-diamond reinforced aluminum matrix composite hot extrusion profiles

[0065]

[0066] It can be seen from Table 1 that with the increase of the content of nanodiamond, the hardness of the hot extruded profile shows an upward trend.

[0067] Example 4 Conventional friction stir coating (FSC)

[0068] The method for preparing a high-hardness and high-wear-resistant coating by using nano-diamond reinforced aluminum-based composite material extrusion profile is as follows:

[0069] (1) The friction stir coating device was debugged, the coating substrate was fixed, and the gap between the coating tool head and the coating base plate was adjusted to 0.6 mm.

[0070] The test used a commercial 1060 aluminum alloy with a size of 120×120×5 mm as the coating substrate, which was purchased from Shenzhen Jinyuanding Hardware Mould Co., Ltd.

[0071] (2) Material preparation: The nano-diamond reinforced aluminum-based composite extrusion profiles obtained in Implementation 1-3 are processed into coating rods suitable for the inner hole shape of the friction stir coating tool head, with a size of 4.9*4.9*20 mm.

[0072] (3) Place the coating rod into the center hole of the friction stir coating tool. Adjust the height of the machine so that the coating contacts the substrate.

[0073] (4) Turn on the friction stir coating machine and coat according to the set coating parameters. The coating parameters are as shown in Table 2 (when the tool head diameter is 11 mm):

[0074] Table 2 Conventional friction stir coating coating parameters

[0075]

[0076] (5) After the coating is completed, the substrate is taken out and cooled naturally. The coating operation is completed, and the coating of the nano-diamond reinforced aluminum-based composite material can be obtained.

[0077] Example 5 Ultrasonic assisted friction stir coating (abbreviated as: UaFSC)

[0078] The method for preparing ultrasonically coated high hardness and high wear-resistant coating by using nano-diamond reinforced aluminum-based composite extrusion profile is as follows:

[0079] (1) The friction stir coating device was debugged, the coating substrate was fixed, and the gap between the coating tool head and the coating base plate was adjusted to 0.6 mm.

[0080] The test used a commercial 1060 aluminum alloy with a size of 120×120×5 mm as the coating substrate, which was purchased from Shenzhen Jinyuanding Hardware Mould Co., Ltd.

[0081] (2) Debugging the ultrasonic assisted device: connecting the ultrasonic assisted device to the friction stir coating device, and using the ultrasonic generator of the ultrasonic assisted device to vibrate the substrate installed on the friction stir coating device.

[0082] The ultrasonic generator was turned on, the workbench vibrated, and the surface of the coated substrate was tested using a CYS-J200 ultrasonic amplitude measuring instrument (Hangzhou Supersonic Electromechanical Technology Co., Ltd.), and it was found that the surface amplitude was uniform. By adjusting the ultrasonic generator (HRK-2012A fully computerized automatic frequency tracking ultrasonic generator, frequency range 20k±400Hz, rated power 2kW, the amplitude ratio of the ultrasonic generator was adjusted to 50%-80%, and the corresponding measured amplitude was within the range of 10-40μm.

[0083] (2) Material preparation: The nano-diamond reinforced aluminum-based composite extrusion profiles obtained in Implementation 1-3 are processed into coating rods suitable for the inner hole shape of the friction stir coating tool head, with a size of 4.9*4.9*20 mm.

[0084] (3) Place the coating rod into the center hole of the friction stir coating tool. Adjust the height of the machine tool so that the coating contacts the substrate, turn on the ultrasonic generator, and make the ultrasonic assist device work normally.

[0085] (4) Turn on the friction stir coating machine and coat according to the set coating parameters. The coating parameters are as shown in Table 3 (when the tool head diameter is 11 mm):

[0086] Table 3 Coating parameters of ultrasonic assisted friction stir coating

[0087]

[0088] (5) After the coating is completed, the substrate is taken out and cooled naturally. The coating operation is completed, and the coating of the nano-diamond reinforced aluminum-based composite material can be obtained.

[0089] Product performance testing:

[0090] 1. Appearance inspection

[0091] Conventional friction stir coating (without ultrasonic assistance) and ultrasonic assisted friction stir coating were used to carry out coating experiments. The experimental effect was on the same aluminum alloy, and the coatings were compared. Figure 1 : Comparison of friction stir coating effects of 0.5% ND / AA6061 composite materials. The left side is the coating without ultrasonic coating, and the right side is the coating with ultrasonic coating.

[0092] Depend on Figure 1 It can be seen that the coating is firmly bonded to the coated substrate. For 6061 aluminum alloy, FSC can achieve a good surface effect. Compared with ordinary FSC, the surface roughness of ultrasonic-assisted friction stir deposition is reduced, and it is more delicate and uniform. Although its surface color is slightly yellowish, the coating has a good appearance overall.

[0093] In the specific experimental process of Example 4 and Example 5, it was found that for the composite material of ND / AA6061 with high hardness and large brittleness, the surface quality of the coating decreased slightly with the increase of ND content, and the machine tool had obvious vibration during the friction stir deposition operation. However, after turning on the ultrasound, the coating process was smoother, the coating surface obtained was wider, and the splash material at the edge of the coating was less.

[0094] 2. Hardness test of coating

[0095] The hardness of the six coating samples obtained in Examples 4 and 5 was tested using a micro Vickers hardness tester (model: MVM-1000A). The indentation force was 0.2 kg, the dwell time was 15 s, and the hardness values ​​in Table 4 and Table 5 were obtained. Figure 2 and Figure 3 .

[0096] Table 4 Comparison of hardness of composite coatings with different nanodiamond contents

[0097]

[0098] Figure 2 This is the hardness distribution diagram of the coating after friction stir coating. Figure 3 is the hardness distribution diagram of the coating after ultrasonic assisted friction stir coating. From Table 4, Figure 2 , Figure 3 It can be seen that:

[0099] (1) The hardness of the coating obtained after friction stir coating treatment is significantly improved (28.89%-57.88%) compared with the hardness of the hot extruded profile. This shows that friction stir coating is beneficial to improving the hardness performance of the composite material. The addition of ultrasonic assistance makes the hardness performance of the coating even better, which can be further improved by 16.78%-38.14%.

[0100] (2) With AA6061 as the substrate, the average hardness of the AA6061 coating can reach about 82.1HV after friction stir coating; the hardness of the coating with a nano-diamond content of 1.5wt.% can reach 135.3HV, which is 62.4% higher than the previous coating. After ultrasonic-assisted friction stir coating, the hardness of the AA6061 coating can reach about 106.4HV, and the hardness of the coating with a nano-diamond content of 1.5wt.% can reach 164.1HV, which is 54.23% higher than the previous coating. This shows that adding a small amount of nano-diamond can greatly improve the hardness of the material.

[0101] 3. Friction and wear rate detection of coating

[0102] The coating samples obtained in Examples 4 and 5 were subjected to wear rate detection. The wear test was carried out on a needle-on-disc friction tester (MPX-3, Jinan Hengxu Testing Machine Technology Co., Ltd.). GCr15 bearing steel with a hardness of 58HRC was used as the counter-grinding disc. Before each test, the surface of the counter-grinding disc was first smoothed with 600# and 1200# sandpapers, and then ultrasonically cleaned in alcohol solution for 10 minutes to remove surface debris and oil stains. The friction and wear sample has a diameter of 5mm and a height of 5mm. The test was first held firmly with a sleeve with an outer diameter of 10mm and then installed on the testing machine. After the sample was made, a layer of 600# and 1200# sandpaper was first fixed on the counter-grinding disc in turn, so that the coating surface was in contact with the sand and was smoothed with the counter-grinding disc before testing. The test was carried out at room temperature, with a rotation speed of 60rpm, a load of 1.5N, and a test time of 120min. The Archimedes drainage method was used before and after the test to measure the mass change before and after friction. The wear rate calculation formula is as follows:

[0103]

[0104] Where W represents the wear rate, the unit is 10 -3 mm 3 / Nm, Q0 is the weight of the sample before the test, Q1 is the weight of the sample after the test, R is the distance from the center of the sample to the center of rotation (equipment fixed value 20.6mm), n is the spindle speed of the testing machine, and F is the friction load.

[0105] Record the experimental data in Table 5 and obtain Figure 4 : Wear rate comparison of six coatings; Figure 5 : Surface image of 1.5% ND / AA6061 after ultrasonic friction and wear test.

[0106] Table 5 Comparison of coating wear rates

[0107]

[0108] From Table 5, Figure 4 and Figure 5 It can be seen that: (1) The addition of nanodiamond can effectively reduce the wear rate of the coating. The wear rate of the friction stir coating on AA6061 substrate is 1.3778×10 -3 mm 3 N -1 m -1 The wear rate of the coating with 1.5wt.%ND@AA6061 is 0.847×10 -3 mm 3 N -1 m -1, which is 38.53% lower than that of the previous treatment. After ultrasonic-assisted friction stir coating, the wear rate of AA6061 coating can reach 0.9531×10 -3 mm 3 N -1 m -1 The wear rate of the coating with 1.5wt.%ND@AA6061 is 0.6889×10 -3 mm 3 N -1 m -1 , which is 26.42% lower than that of the aluminum-based composite material. This indicates that the addition of nano-diamonds to the aluminum-based composite material can effectively improve the wear resistance.

[0109] (2) The wear rate of the coating obtained by ultrasound-assisted coating is lower than that of the coating obtained by conventional friction stir coating, and the wear rate can be reduced by 11-31%, indicating that ultrasound-assisted coating can effectively improve the wear resistance of the coating.

[0110] (3) By Figure 5 It can be seen that after the friction and wear test, a Cr-rich mechanical mixed layer is formed on the surface of the 1.5% ND / AA6061 ultrasonic-assisted friction stir coating coating in the wear test with Gr15, so it has higher wear resistance, and its loss rate is only 50% of that of the friction stir coated AA6061 coating.

[0111] 4. Grain size detection of extruded profiles and coated coatings

[0112] The hot extruded profiles obtained in Examples 1 and 2 and the AA6061 coating and 0.5% ND / AA6061 coating obtained in Example 4 were subjected to EBSD detection to obtain Figure 6 , Figure 7 .

[0113] Figure 6 EBSD images of hot extrusion profiles, where (a) is AA6061 hot extrusion profile; (b) is 0.5% ND / AA6061 hot extrusion profile. Figure 6 It can be seen that the hot extruded material obtained by the present invention is dense and has no defects such as micropores or cracks. The particle size of AA6061 is greater than 3.84 μm, and the grains are relatively coarse. The nano-diamond particles and aluminum powder are subjected to high-speed ball milling to obtain a good primary dispersion effect. The average particle diameter of 0.5% ND / AA6061 after hot extrusion is 1.67 μm, but the coarseness of the grains is not uniform enough.

[0114] Figure 7 The microstructure diagrams of the coatings, where (a) is the AA6061 coating and (b) is the 0.5% ND / AA6061 coating. Figure 6 and Figure 7By comparison, after friction stir coating, the grain size of the coating is much more uniform and smaller than that of the hot extruded material. The grain size of the 0.5% ND / AA6061 coating reaches 0.88μm, reaching the ultrafine grain standard (<1μm).

[0115] 5. Detection of the interface between the coating deposition layer and the substrate

[0116] The strong bond between the coating and the substrate surface is not only part of the coating quality, but also a prerequisite for the continuous AFSD process. The coated sample to be tested was first etched with 20% NaOH solution for 15 seconds so that the coating and the substrate could be clearly distinguished, and then placed under an optical microscope (OM) for observation.

[0117] Figure 8 a and b show the cross-sectional OM images of the friction stir coating bonding interface. Before OM imaging, all samples were etched with 20% NaOH solution for 15 s. Figure 8 a and b show that there is a continuous bonding interface between the AA6061 and ND / AA6061 coatings and the substrate without cracks or pores. Figure 8 c and d show the EBSD images of the coating bonding interface. Figure 8 c shows that the AA6061 coating and substrate materials have been cross-fused without obvious boundaries, which will bring strong metallurgical bonding to the bonding interface. The large grains of the substrate are elongated, and there are many LAGBs within the grains, indicating that the recrystallization of most of the substrate grains near the bonding interface is incomplete. In contrast, there is a clear boundary between the 0.5ND / AA6061 coating and the coating grains are significantly smaller than the substrate grains. Figure 8 d The grain size ratio of the substrate Figure 8 c is much smaller. This is because the hardness of the 0.5% ND / AA6061 feed rod is much higher than that of AA6061, which leads to the intensified stirring of the substrate material by the feed rod during the AFSD process, resulting in a more complete recrystallization of the substrate and a finer grain structure. This strong stirring is also conducive to destroying the aluminum oxide film on the contact surface and enhancing the metallurgical bonding strength of the joint interface. In addition, Figure 7 b shows that the 0.5% ND / AA6061 coating-substrate bonding interface is jagged. This non-planar interface forms a mechanical interlocking structure and also improves the interfacial bonding strength.

[0118] The above is only a preferred embodiment of the present invention. It should be noted that the above preferred embodiment should not be regarded as limiting the present invention. The protection scope of the present invention should be based on the scope defined by the claims. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the spirit and scope of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A method for preparing a high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite material coating, characterized in that: The steps include: (1) Weigh nano-diamond and aluminum raw materials according to the ratio, put the raw materials into a steel can, put the steel can into a ball mill, and ball mill under an inert gas atmosphere, add 1%-2.5% stearic acid as a control agent to the raw material powder, and ball mill to obtain a mixed material powder; The raw materials of the nano-diamond and aluminum are as follows by weight percentage: Al: 98.5-99.5%, nano-diamond: 0.5-1.5%; (2) Heat the mixed material powder to 280-430°C and keep it warm for 1 hour to degas; (3) The mixed material is then placed in a powder cylinder of a sample preparation device, heated to 120°C-150°C and dried for 20-30 minutes, and then the powder is compressed under a pressure of 400 MPa; (4) Raise the temperature to 480°C, keep the temperature for 20-30 minutes, apply a pressure of 790 MPa for the first compression, then raise the temperature to 500-540°C and keep the temperature for 20-30 minutes, and then apply a pressure of 790 MPa for the second compression; (5) The composite material blank treated in step (4) is heated again to 450-510°C, kept at this temperature for 20-30 minutes, and then placed under a press for hot extrusion; thus, a hot extruded profile of a nano-diamond reinforced aluminum-based composite material is obtained; (6) Processing the hot extruded profile of the nanodiamond reinforced aluminum matrix composite material into a coated rod; (7) Place the coating rod into the center hole of the friction stir coating device and adjust the height of the machine tool so that the coating rod contacts the substrate; (8) Starting the machine tool of the friction stir coating device and performing coating processing according to the set coating parameters; the coating parameters are a translation speed of 24-25 mm / min, a downward speed of 7-10 mm / min, and a rotation speed of 5000-8000 r / min; (9) After coating, the substrate is taken out and cooled naturally. The coating operation is completed, and a high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite material coating is obtained.

2. The method for preparing the high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite material coating according to claim 1, characterized in that: The ball mill in step (1) uses steel balls as the ball material, and the ball milling parameters are: rotation speed of 500-600 rpm, alternating time of 10-15 min, ball-to-material ratio of 8-10:1, ball milling time of 8-9 h, and argon as the inert gas.

3. The method for preparing the high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite material coating according to claim 1, characterized in that: The specific steps of step (3) are as follows: before putting the material, two pads are placed at the bottom of the powder cylinder, a 2-5 mm graphite powder layer is placed between the two pads, the graphite powder is compressed with a pressure of 200-300 MPa to increase the sealing performance, and a layer of graphite paper is pasted on the inner wall of the powder cylinder to reduce friction; After adding the mixed material powder, heat it to 120℃-150℃ and dry it for 20 minutes, then put in the upper pressure pad, and then put a 2-5mm thick layer of graphite powder on the upper pressure pad to increase the sealing, put in the push rod for compression, and compress the mixed material powder with a pressure of 400MPa for 1-5min.

4. The method for preparing the high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite coating according to claim 1, characterized in that: The specific steps of step (4) are as follows: first, the temperature is raised to 480°C, kept at this temperature for 30 minutes, and a pressure of 790 MPa is applied for the first compression, and the compression time is 1-5 minutes; then the temperature is raised to 500-540°C and kept at this temperature for 30 minutes; then a pressure of 790 MPa is applied for the second compression, and the compression time is 1-5 minutes.

5. The method for preparing the high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite material coating according to claim 1, characterized in that: The specific steps of step (5) are as follows: remove the heating sleeve of the sample preparation device, then remove the cushion block, place the powder cylinder directly on the support block, align the center of the powder cylinder with the support block, start the lower pressure rod of the press, push out the two pressure pads at the bottom of the barrel, then reverse 180 degrees, use the pressure rod to press the composite material blank back to the middle, then put the profile mold into the powder cylinder, install the cushion block, reverse 180 degrees and place it on the support block, align the centers, put down the heating sleeve, reheat to 450-510°C, keep warm for 30 minutes, and then put it into the press for hot extrusion.

6. The method for preparing the high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite material coating according to claim 1, characterized in that: In the step (7), the gap between the coating tool head of the friction stir coating device and the substrate is pre-adjusted to a distance of 0.2-1.5 mm, which is consistent with the desired coating thickness.

7. The method for preparing the high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite material coating according to claim 1, characterized in that: The method also includes connecting an ultrasonic auxiliary device to the friction stir coating device before step (8), and using an ultrasonic generator of the ultrasonic auxiliary device to vibrate the substrate mounted on the friction stir coating device.

8. The method for preparing the high-hardness and high-wear-resistant nano-diamond reinforced aluminum-based composite coating according to claim 7, characterized in that: The frequency range of the ultrasonic generator is 20k±400 Hz, the rated power is 2 kW, and when the amplitude ratio of the ultrasonic generator is adjusted to 50%-80%, the corresponding measured amplitude is in the range of 10-40 μm.

Citation Information

Patent Citations

  • Preparation method for carbon-nanotube-reinforced zinc-based composite

    CN107245596A

  • Nanometer Al4C3 reinforced aluminum-based composite material and preparation method thereof

    CN113199027A